Upcycling lignosulfonate into bio-based polyhydroxybutyrate films for eco-friendly antimicrobial and antioxidant food packaging - Chysirichote, Teerin; Phaiboonsilpa, Natthanon; Sakoolkaew, Prueksuda (My University, 2026)
BACKGROUND: This study explored the upcycling of lignosulfonate, a by-product of the pulp and paper industry, into polyhydroxybutyrate (PHB)-based films for sustainable food packaging applications. Glycerol and lignosulfonate were incorporated to enhance film flexibility, antioxidant activity, and antibacterial properties, addressing the growing demand for functional and eco-friendly packaging materials. RESULTS: Glycerol increased film thickness and water vapor permeability but reduced tensile strength, confirming its plasticizing effect. The incorporation of lignosulfonate improved barrier and functional properties by reducing water uptake, enhancing antioxidant capacity, and inhibiting Staphylococcus sp. When applied to choux cream, the optimized lignosulfonate–PHB film (245 g kg−1 glycerol, 120 g kg−1 lignosulfonate) markedly suppressed microbial proliferation, showing the lowest growth rates (μ = 0.56 log CFU g−1 d−1 for total plate count and 0.35 log CFU g−1 d−1 for yeast and mold count at 30 °C) and temperature coefficients (Q₁₀ = 2.16 and 1.78, respectively). This indicates strong thermal stability and effective control of microbial spoilage across 10–30 °C storage. CONCLUSION: Lignosulfonate-based PHB films demonstrate high potential as biodegradable and functional food packaging materials. Their ability to extend shelf life and maintain microbial stability supports the transition toward sustainable, clean-label, and low-emission packaging solutions. © 2025 Society of Chemical Industry.
Keywords: active packaging; biodegradable plastics; food shelf life extension; polyhydroxyalkonates